1988
DOI: 10.1111/j.1600-0897.1988.tb00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Histocompatibility Antigens and Habitual Abortion

Abstract: Eighty-five couples with habitual abortion were studied: 43 were primary aborters (i.e., had no advanced pregnancy beyond 20 weeks gestation), and 42 were secondary aborters. The only significant finding in primary female aborters was a reduction in the incidence of B35. In contrast, in secondary female aborters there was a reduction in the incidence of DR3 and A1/B8/DR3 and an increase in the degree of homozygosity of HLA B. In the male partners of primary aborters, there was a reduced incidence of DR3 and A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Concerning HLA class I antigens, Cauchi et al reported that HLA-B35 was significantly lower in patients with unexplained recurrent abortion compared with a control population [4], which is in good agreement with the results of this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Concerning HLA class I antigens, Cauchi et al reported that HLA-B35 was significantly lower in patients with unexplained recurrent abortion compared with a control population [4], which is in good agreement with the results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…In this context, there have been reports concerning the frequency and sharing of HLA antigens in couples who experienced recurrent spontaneous abortions. Recent investigations, however, demonstrated that the incidence of shared HLA antigens was not significantly higher in couples with unexplained recurrent abortions [4,5,21,27,33]. Recent investigations, however, demonstrated that the incidence of shared HLA antigens was not significantly higher in couples with unexplained recurrent abortions [4,5,21,27,33].…”
Section: Discussionmentioning
confidence: 96%
“…absence of anti-paternallymphocytotoxic antibodies," increased paternal HLA sharing, 8,9 and increased homozygosity for HLA loci. ll, 12 There is conflicting data in relation to most ofthese parameters, however. Other studies have shown that there is no association of recurrent abortion with increased HLA sharingr' or lack of maternal serum blocking antibodies in MLR.…”
Section: Introductionmentioning
confidence: 99%
“…11-14,2o And there are some reports that the failure of maternal recognition was due to significant HLA sharin~between couples of unexplained recurrent abortions.l ': 5 Recent reports, however, have demonstrated that sharing ofHLA antigens was not significantly increased overall within couples with recurrent abortions compared with controls. [18][19][20] We previously reported that significant compatibility was not observed with the HLA-A,B,C antigens in couples with a history of unexplained recurrent abortions, whereas the significant compatibility was obtained with HLA-DR antigens.P" It is well recognized that there is strong linkage disequilibrium between the HLA-DR and HLA-DQ antigens because of very close…”
Section: Discussionmentioning
confidence: 99%